Hubungan Antara Dukungan Sosial Keluarga dengan Motivasi Belajar Pada Siswa SMP - Desitasari, Nediawati; , Drs. Soleh Amini Yahman M.si, Psi (2017)
Education is one factor that can not be separated from one's life, whether in family, community and nation. Education aims at educating the nation also while enhancing human dignity. Through education that is expected to be achieved towards the improvement of human life is perfect. Is to achieve it, of course, the education required a huge motivation, so that all obstacles that come up can be overcome. The most important motivation for education is achievement motivation, where a person is likely to struggle to achieve success or choosing an activity-oriented for the purpose of success or failure. In reality, not all students have high motivation to learn, it is marked with the student's behavior such as skipping, cheating and late assignment. Based on the results of a survey conducted by researchers at the Saturday October 8, 2016 on one counselor / BK in SMP Muhammadiyah 1 Sragen, according to the data that has been processed student about the behavior of students who have missed classes. Of the total percentage of all students, 23.5% of class VII, VIII grade of 46.3%, and 30.2% of class IX. This study aims to determine the relationship between social support of families with the motivation to learn, and the effective contribution of family support on motivation to learn. The hypothesis is a positive relationship between social support of families with the motivation to learn in junior high school students. Subjects in this study were students of SMP Muhammadiyah 1 Sragen class VIII as many as 101 people and taken with quota sampling technique. The instruments used were is the scale of learning motivation and social support of families. The data were analyzed by using analysis of product moment. The results of the study conveniently indicates: (a) There was a significant relationship between social support of families with the motivation to study (r = 0.648;p = 0.00), (b) family social support contribute to motivation to learn (R2 = 0.420). The second variable is motivation to learn, and family support have a high categorization. The results of studies suggest the importance of family support on motivation to learn.